Acute pancreatitis: Comparison of scoring systems in predicting its severity - Bajracharya, Sandeep Raj; Peeyush, Denis; Pradhan, Bickram (Birat Journal of Health Sciences, 2024)
Background: Acute pancreatitis (AP) is an inflammatory process with a highly variable clinical course. So an early, quick and accurate scoring system is necessary to stratify the patients according to their severity. Our aim was to study the usefulness of scoring systems in predicting the severity of AP. Methods: This is a comparative cross sectional observational study on 51 patients admitted with the diagnosis of AP from June 2021 to December 2021. Ranson, Acute Physiology and Chronic Health Evaluation (APACHE) II, Bedside Index of Severity in Acute Pancreatitis (BISAP), Computed Tomography Severity Index (CTSI) of all patients were calculated. Serum C-reactive protein (CRP) levels were measured at admission (CRPadm) and after 48 hours (CRP48). Result of these was compared with that of revised Atlanta classification. The predictive accuracy of each scoring system was measured by the area under the receiver-operating curve (AUC) Results: Of 51 cases, 7 (13.7%) were graded as severe AP. The AUC for APACHE II was the highest for predicting severe acute pancreatitis 0.765 (95% CI: 0.578-0.951). Ranson was the second most accurate in predicting severe acute pancreatitis 0.763 (95% CI: 0.547-0.979). CTSI had a high sensitivity for predicting severe AP 85.71 (95% CI: 42.13- 99.64) and CRP48 had a high specificity for predicting severe AP 90.91 (95% CI: 78.33- 97.47). Ranson’s score had high negative predictive value for predicting severe AP 94.29 (95% CI: 83.48-98.18). Conclusion: Similar predictive accuracy was shown by various scoring systems used in this study for severity of AP. To achieve further improvement in prognostic accuracy unique models are needed.